Sustaining training effects through physical activity coaching (STEP): a randomized controlled trial - Matthias Loeckx; Fernanda M. Rodrigues; Astrid Blondeel; Stephanie Everaerts; Wim Janssens; Heleen Demeyer; Thierry Troosters (BMC, 2023)
Abstract Background Pulmonary rehabilitation (PR) programs improve physical fitness, symptoms and quality of life (QoL) of patients with COPD. However, improved physical activity (PA) is not guaranteed after PR and the clinical benefits fade off after PR discharge. We aimed to investigate whether a 9 months PA-telecoaching program is able to improve PA of patients with COPD, after 3 months of PR and if this leads to maintenance of PR-acquired benefits. Methods Patients with COPD enrolled in a 6-month PR program were randomized to a (semi-automated) PA-telecoaching program or usual care, 3 months after PR initiation. The intervention consisted of a smartphone application with individual targets and feedback (for 6 months) and self-monitoring with a step counter (for 9 months). Patients were followed up for 9 months after randomization. Primary outcome was PA (daily step count by accelerometery), secondary outcomes were exercise tolerance, quadriceps force, dyspnea and QoL. Results Seventy-three patients were included (mean ± SD: 65 ± 7 years, FEV1 49 ± 19%, 6MWD 506 ± 75 m, PA 5225 ± 2646 steps/day). The intervention group presented a significant improvement in steps/day at every visit compared to usual care (between-group differences mean ± SE: 1431 ± 555 steps/day at 9 months after randomization, p = 0.01). Secondary outcomes did not differ between the groups. Conclusion The semi-automated PA-telecoaching program implemented after 3 months of PR was effective to improve the amount of PA (steps/day) during PR and after follow-up. However, this was not accompanied by the maintenance of other PR-acquired benefits. Trial registration ClinicalTrials.gov. Identifier: NCT02702791. Retrospectively registered on March 9, 2016. Start study October 2015. https://clinicaltrials.gov/ct2/show/NCT02702791?term=NCT02702791&draw=2&rank=1 .